Phenotype and genotype characterization, feeding habit and reproductive biology of crossbanded barb, Puntioplites bulu (Bleeker, 1851) from Peninsular Malaysia - A. Ghani, Intan Faraha (2019)
Puntoplites bulu is a freshwater Cyprinidae and widely distributed in Southeast Asia. It has attracted considerable interest due to high demand and price. However, an apparent decline in its distribution and abundance is observed and this is due to several factors, such as habitat degradation, pollution and overfishing. Little is known about the biology and population structure of this valuable freshwater species. Therefore, this study was to investigate its population morphological difference, genetic diversity, reproductive biology and feeding guild of P. bulu in Peninsular Malaysia. Meristic, morphometric characters and truss network analysis were used in discriminant analyses to study the intraspecific variation of wild P. bulu stock from three major rivers (Perak River, Pahang River and Kelantan River) in Peninsular Malaysia. Morphometric characters variations were apparent with samples from Perak River and were found to have longer pre-occipital length, pre-operculum length and caudal peduncle length, while samples from Kelantan River were found to have longer length from pelvic fin base to anal fin base. Further, based on truss network analysis, differences were observed mainly on head and caudal region with samples from Perak River population had smaller head and longer caudal area. Intraspecific variation of P. bulu from the three major rivers was also determined based on genetic divergence by using mitochondrial DNA (mtDNA). Two distinct genetic lineages were apparent viz Central West and East Peninsular Malaysia with natural barriers (the Titiwangsa Range) acted as natural dividers between these two lineages. Alternatively, the close genetic relation and haplotype sharing that were observed between Perak and Kelantan populations could be due to human translocations. Further, haplotype sharing between Kelantan and Pahang populations revealed the migration ability of P. bulu through ancient connectivity. Food items of P. bulu from Perak River revealed a planktivorous feeding habits. They consumed more plant matter based food item with Bacillariophyceae as the major diet item based on a simple resultant index of 29.9%, Crustacea (21.26%), Chlorophyceae (10.6%), detritus (14.88%), Mollusca (12.65 %) plant matter (9.92%), and worms (0.8 %). High food overlap was observed between adult and juvenile stages, although ontogenetic dietary changes were observed between these two stages with adults consuming a larger prey size while juveniles feed primarily on smaller items. Some aspects of reproductive biology of P. bulu were determined from the Perak River. Asynchronous ovarian development patterns were observed and spawning season happened in October and May, coincided with rainfall period. The sex ratio of P. bulu during the study period was 1:1.14, though the females predominated in almost every month. Mature size for females and males was in the range of 25-30 cm and 20-25 cm, respectively. Absolute fecundity ranged from 1,631 to 31,059 per ovary and it was highly related to ovary weight and gonadosomatic index (GSI) rather than body weight and total length. In conclusion, morphological divergence and two distinct genetic lineages of P. bulu were observed between the three major rivers in Peninsular Malaysia. They are planktivorous and had an asynchronous ovary development pattern with spawning season coincided with rainfall. Information from this study useful to facilitate the management of this valuable species.